(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Personal brand orientation has become a critical issue, enabling SMEs to gain a significant competitive advantage, particularly in markets where personalities influence followers’ actions on social media commerce. This study proposes and empirically validates a theoretically structured approach for assessing personal brand orientation, its antecedents, and implications for the performance of digital firms. The model distinguishes between personal characteristics of SMEs owners such as narcissism, vision, and educational background as antecedents of personal brand orientation and correlates them with the performance of digital firms in social commerce in Indonesia. A purposive sample of 355 respondents completed an online survey questionnaire, with each respondent representing one SME organization. Owner narcissism, owner vision, owner education background, personal brand orientation, and digital firm performance were all included in the questionnaire, which was adapted from previous studies. A five-point Likert scale was used to evaluate each item. To test the proposed research hypotheses, structural equation modeling (SEM) was used. Later confirmation of this study’s positive relationship between owner vision and owner education for personal brand orientation based on upper echelon theory. On the other hand, owner narcissism was found to have a detrimental effect on personal brand orientation. This study discovered a significant correlation between personal brand orientation and the performance of digital firms. This notion implies that SMEs that rely on their owner’s social media popularity can improve their performance by effectively communicating their vision to their team, leveraging the owner’s relevant education and expertise, and increasing personal brand-related strategies at the marketing level within the organization.